(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
In human thought, the concept of “fate” embodies elements such as predestination in life, will, and the outcome of events. This concept is reflected differently in different languages and cultural contexts. In linguistics, in particular in linguistic philosophy and language-cultural theories, it is important how language imagines and expresses the world. Therefore, through the units expressing “fate” in Uzbek and English, a linguistic worldview can be revealed. As an introduction, attention is paid to the principle that language reflects worldview forms and the harmony of language and culture. For example, language, in addition to materiality, also carries the spiritual aspect and determines a person’s attitude to his world. Language is a reflection of human thought, which embodies the history, religion, values, and outlook on life of the people. The language of each nation reflects how it perceives the world, what values it prioritizes, what events it considers important. Therefore, how the concept of “taqdir” is expressed in the language shows the people’s philosophy of life. The Uzbek people have long considered fate to be an integral part of life. Expressions such as “Yozilgan bo‘lsa, bo‘ladi”, “Har kimning taqdiri peshonasida yozilgan” are widespread among the people. These expressions show a person’s faith in life, patience, and submission to the will of God.